Penyuluhan Dan Edukasi Tentang Penyakit Hipertensi - Hikmah, Yevi Ade; Agustian , Tri Koko; Anggraeni , Maisa; Faza , Nida Nadhirah; Winata, Yulia Adevia; Sari , Lezi Yovita Sari; Rohani , Tuti; Azissah , Danur (Jurnal Kewirausahaan dan Bisnis, 2025)
Hypertension Systolic and diastolic blood pressure increases. Hypertension is a diverse group of diseases and is known to be a fatal disease. High blood pressure is a risk factor for premature death, heart failure and brain disease. According to WHO data in 2015, around 1.13 billion people worldwide suffer from hypertension, which means one in three people worldwide are diagnosed with hypertension. This number will continue to increase every year. It is estimated that by 2025, 1.5 billion people will suffer from hypertension, and hypertension and its complications will cause 10.44 million deaths every year. Age and social and economic factors can influence hypertension. The risk of high blood pressure increases with age. This is caused by structural changes in large blood vessels, leading to narrowing of the lumen, hardening of the walls, and increased blood pressure. If not controlled, hypertension can cause complications such as coronary heart disease and stroke, heart failure, kidney failure, peripheral vascular disease and damage to retinal blood vessels which results in visual impairment. This community service has been carried out from January 20 2025 to January 31 2025. Evaluation of activities is based on health education activities for hypertension sufferers. Then, data was obtained on people suffering from hypertension in the village of Delima village, to provide advice and education to the public about hypertension.